Usulan peningkatan kualitas produk briket arang kelapa - Hadisantono; Theodorus B. Hanandaka; Parama Kartika Dewa; Joseph Juan Emiton (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
CV Jumbuh is a company that produces charcoal briquettes made from coconut shells. It is located in Klaten, Central Java. The defective products is a problem that is solved in this research because it produces a defect percentage of 15% per month. This company continues to strive to improve product quality so that buyers can increasingly trust it. This research aims to reduce the monthly percentage of defective products to a maximum of 10% per month by proposing several improvement solutions. This research uses the Statistical Process Control method. This research succeeded in identifying the most common types of defects, namely crack defects (43.6%), moisture content defects (40.4%), and ash defects (15.9%). Based on the results of discussions with stakeholders, the solution implemented was the creation of Standard Operational Procedure (SOP) for each production process. This SOP will be equipped with a quality inspection check sheet and machine inspection checklist. Implementation of the solution resulted in a reduction in the percentage of defects to 6% per month.